UPAYA MENINGKATKAN PEMBELAJARAN TOLAK PELURU YANG EFEKTIF DENGAN METODE PAKEM PADA SISWA KELAS V SD N 163/8 MUARA TABIR TEBO - DEKA ISMI MORI SAPUTRA; Subarjo subarjo (Jurnal Muara Pendidikan, 2018)
The difficulty of students in carrying out basic techniques on learning material to shot put is the background of this study. There were still many students who have not been correct in carrying out a series of repulsion movements. This study aims to determine the application of the PAKEM (Active, Creative, Effective and Fun Learning) method to improve learning of shot put to students in the 5th grade students of SDN 163/8 Muara Tabir Tebo.The research method used PTK design which was carried out in two cycles. The subjects of this research were 24 students of the 5th grade students of SDN 163/8 Sungai Jernih Muara Tabir, Tebo. The data of shot put results were obtained through performance tests and observation sheets were used to collect data on student activities in following the learning process of shot put using the PAKEM method. The results of this study were obtained based on the assessment of three aspects namely psychomotor, affective, and cognitive. The results of the assessment shown that there was a significant increase from the condition of cycle I to cycle II. The results of the assessment of learning shot put obtained from the first cycle were as many as 15 students or the percentage of completeness 71.3%. Whereas in cycle II there was an increase to 20 students or the percentage of completeness to be 83, 3%. Based on the results of the study, it was concluded that learning shot put through the PAKEM method can improve the learning outcomes of the fifth grade students of SDN 163/8 Sungai Jernih Muara Tabir.